Reevaluation of the arterial blood supply of the auricle. Issue 2 (11th October 2016) - Zilinsky, Isaac; Erdmann, Detlev; Weissman, Oren; Hammer, Niels; Sora, Mircea‐Constantin; Schenck, Thilo L.; Cotofana, Sebastian
Abstract: The anatomical basis for auricular flaps used in multiple aesthetic and reconstructive procedures is currently based on a random distribution of the underlying arterial network. However, recent findings reveal a systematic pattern as opposed to the present concepts. Therefore, we designed this study to assess the arterial vascular pattern of the auricle in order to provide reliable data about the vascular map required for surgical interventions. Sixteen human auricles from eight body donors (five females/three males, 84.33 ± 9.0 years) were investigated using the unique 'Spalteholz' method. After arterial injection of silicone, a complete transparency of the tissue was achieved and the auricular arteries and branches were visible. Qualitative and quantitative evaluation of the arterial vascular pattern was performed. The superior and the inferior anterior auricular artery provided the vascular supply to the helical rim, forming an arcade, i.e. helical rim arcade. On the superior third of the helical rim another arcade was confirmed between the superior anterior auricular artery and the posterior auricular artery (PAA), i.e. the helical arcade. The perforators of the PAA were identified lying in a vertical line 1 cm posterior to the tragus, supplying the concha, inferior crus, triangular fossa, antihelix and the earlobe. The results of this study confirmed the constant presence of the helical rim arcade (Zilinsky‐Cotofana), consistent perforating branches of the PAA, and the helical arcade (Erdman), and will help and guide physicians performing auricular surgeries toward fast and simple procedures with optimal patient satisfaction.